Four 3D Cd(II)-based metal organic hybrids with different N,N `-donor spacers: syntheses, characterizations, and selective gas adsorption properties - Bhattacharya, Biswajit; Dey, Rajdip; Pachfule, Pradip; Banerjee, Rahul; Ghoshal, Debajyoti (Crystal Growth & Design, 2013)
{Four new metal organic frameworks with bivalent cadmium, disodium succinate (Na(2)suc), and four different N,N'-donor ligands, i.e., {[Cd(L1)(suc)]center dot(H2O)(3)}(n) (1), {[Cd(L2)(suc)]center dot(H2O)(2)\